Enunciar-se, organizar-se, controlar-se: modos de subjetivação feminina no dispositivo da maternidade - Fabiana de Amorim Marcello (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2005)
The purpose of this article is to analysethe way in which the motherhood role isorganised in the media, producingspecific modes of female subjectivation.Based on a Foucaultian framework, Icharacterise enunciating oneself,organising oneself and controllingoneself as techniques of the self used bythe mother-subjects. I thus undertake adiscursive analysis of two sets ofmaterials: one consisting of articlesfrom the magazines Veja and Caras,from 1992 to 2002, about famousmothers (Cássia Eller, LucianaGimenez, Vera Fischer and Xuxa); and,the other, consisting of articlespublished in the magazine Crescer,between January 2001 and July 2002. Ishow how this mechanism organisesthese techniques of the self in order tocreate a logic where the mother-indivi-dual is asked to focus on herself andconsider that taking care of herself istaking care of the other (her son) and,in this way, leading the mother-individuals to recognise themselves asobjects visible to themselves and toenunciate themselves as subjectstransformed by maternal practices.